Hypothermia in neonates born by caesarean section at a tertiary hospital in South Africa - Patel, Mariambibi; Ramagaga, Neo; Kruger, Danielle; Lehnerdt, Grace; Mansoor, Imraan; Mohlala, Lesedi; Rendel, Dylan; Zaheed, Fathima; Jordaan, Mimie; Mokhachane, Mantoa; Nakwa, Firdose Lambey; Mphahlele, Ramatsimele (Frontiers in Pediatrics, 2022)
Introduction neonatal hypothermia has previously been noted in a large proportion of neonates born through Caesarean section at Chris Hani Baragwanath Hospital (CHBAH), yet no study in South Africa specifically explores the extent and severity of the threat of hypothermia to this population of neonates. Objectives to describe the proportion and severity of neonatal hypothermia in infants born via Caesarean section at CHBAH as well as to document and describe possible contributing factors to neonatal hypothermia in this population. Methods A neonatal unit's database records were reviewed for demographic information of patients and their mothers, clinical characteristics, body temperature and outcomes. Comparisons between normothermic and hypothermic neonates were performed. Results Forty-one percent of neonates born via Caesarean section had hypothermia at birth, of whom 71%, 27% and 2% had mild, moderate and severe hypothermia, respectively. Prevalence of admission hypothermia was 42%. On average, neonates were born at term and were of normal birth weight. No maternal factors were found to be statistically significant. Bag-mask ventilation (BMV) and cardiopulmonary resuscitation (CPR) [3.4% vs. 0.7%, p-0.033; OR 2.67 (95% CI: 1.06–6.77)] and an elevated lactate [13.25 vs. 3.2 mmol/l, p-0.032; OR 1.13 (95% CI: 1.01–1.26)] were associated with hypothermia. In the multivariable logistic regression analysis hypothermia in neonates was associated with an elevated lactate. Conclusions Prevalence of hypothermia in neonates born by Caesarean section is high and further prospective studies are required to elucidate the factors contributing to this.